2008
DOI: 10.1021/cm8027912
|View full text |Cite
|
Sign up to set email alerts
|

Nanosheet Seed-Layer Assists Oriented Growth of Highly Luminescent Perovskite Films

Abstract: Oxide phosphors are attractive materials for various applications in optoelectronic devices due to their high chemical stability and efficient luminescent characteristics. As yet, however, the fabrication of high-quality luminescent thin films on a glass substrate remains challenging for practical implementation. Here, we report the efficient fabrication of highly oriented luminescent perovskite oxide films on a glass substrate using a monolayer film of oxide nanosheets as the seed layer. A densely packed mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 21 publications
(26 reference statements)
3
33
0
Order By: Relevance
“…Lu et al [5] unambiguously showed that the stretching mode of the terminating Nb-O bond in a polyoxoanion NbW 3 second highest antisymmetric modes reaches 1.39, being unacceptably larger than 956/791 (the present experimental data). In addition, it is not obvious whether introduction of double bonds decreases this energy ratio.…”
Section: Appendixsupporting
confidence: 46%
See 2 more Smart Citations
“…Lu et al [5] unambiguously showed that the stretching mode of the terminating Nb-O bond in a polyoxoanion NbW 3 second highest antisymmetric modes reaches 1.39, being unacceptably larger than 956/791 (the present experimental data). In addition, it is not obvious whether introduction of double bonds decreases this energy ratio.…”
Section: Appendixsupporting
confidence: 46%
“…3 and used as the "mother" suspension. This mother suspension was diluted to 4.0  10 -3 g L -1 by adding pure water with a resistivity higher than 1.8  10 7 cm provided by a Millipore Milli-Q system in order to be used as the subphase in the LB technique.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The residue after the post-treatments was curtained as ammonium and/or oxonium ions in the intersheet galleries, along with some water molecules [3,19,31]. The broad peaks may be related with the misalignment of the nanosheet crystallites [20]. Such polymer-free multilayer films of La 0.90 Dy 0.05 Nb 2 O 7 nanosheets allow us to perform the following PL experiments to avoid the possible interference with the intercalated polymer.…”
Section: Film Fabricationmentioning
confidence: 99%
“…In particular, it is attractive to use them to fabricate multilayer composite films on a glass substrate through the layer-by-layer (LBL) assembly technology, based on the alternate adsorption with suitable polymeric cations [18][19][20][21][22][23][24]. After followed by ultraviolet light exposure or heat treatment, the organic cations will be decomposed completely, which leads to the formation of transparent polymer-free nanosheet multilayer films deposited on the substrate [22][23][24].…”
Section: Introductionmentioning
confidence: 99%